Design of band-pass filters by experimental and simulation methods at the range of 100-125 keV of X-ray in fluoroscopy. (30th May 2022) - Khaleghi, Goli; Soltani-Nabipour, Jamshid; Khorshidi, Abdollah; Taheri, Fariba
The determination of filters that remove low-energy and attenuate high-energy spectra does not essentially influence image quality, so it can reduce the absorbed patient dose. This work examines the impacts of thickness and filter material on contrast, resolution, absorbed patient dose and image quality. Based on the attenuation curves of elements and taking into account the cost-effectiveness and availability factors, four elements including tin, tungsten, lead and copper in different thicknesses was studied at the range of 100-125 keV. The simulations were executed using MCNPX code with an error less than 1% that represented the accuracy. Experimental data were obtained based on the results of calculations and simulations using fluoroscopy equipment. The results showed that applying the filters caused improving the resolution and image quality, and also remarkable reduction in output dose rate. In conclusion, the 0.1 mm thick lead element was taken as the most appropriate element in filtration.